Penghasilan modul bahasa pengaturcaraan c untuk pelajar-pelajar BTI 2133 Kolej Universiti Teknologi Tun Hussein Onn - Masrom, Nor Ratna (2002)
The government realized about the emergence of ICT as an economic means and as the economic engine that is able to spear ahead the country's economy in the era of globalization. The MSC obviously a prove about our belief on the potential of ICT. The education institution is a main platform for the purpose of continuation, follow through, main deciding factor of the direction and power any given communities to generate graduate that is competence and has high quality. So it is the responsibility of the institute to prepare the education material for enhancement of understanding like module preparation, CD etc, including the effort to improvise the module must be done so that the time, money and energy can be minimize. In this survey, 54 students of BTI 2133 has been chosen as sample and it was found out that they have high level of knowledge on the programming language. So the researcher has to provide a suitable module with their level of knowledge. Beside that there is significant difference between the old and new model which has been modified. There is also significance relation between understanding and presentation technique, understanding and assessment technique, and understanding and explanation. However all three factors give small influence in improving of understanding.